Seed-fruit relationships in fleshy fruits: Role of hormones. A review - Balaguera-López, Helber Enrique; Fischer, Gerhard; Magnitskiy, Stanislav (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Seeds are known to have significant biological importance in nature, and they have high economic value in agriculture. This review discusses the physiological, biochemical, and hormonal aspects involved in the seed-fruit relationship, highlighting the main implications that seeds have on fruit set and growth, development, and abscission of some fleshy fruits. Fleshy fruits, with the exception of some parthenocarpic species, require pollination and double fertilization for seed formation. This contributes to the stimulation of hormone synthesis for auxins, gibberellins, cytokinins, and brassinosteroids. These hormones are required for seed formation and, in turn, for fruit development; and they determine fruit set, final fruit size, fruit shape and quality characteristics in some fruits. This knowledge is necessary for successful management of the cultivation of species producing fleshy fruits.